Therapeutic Effect of Trisodium Phosphonoformate on Cutaneous Herpesvirus Infection in Guinea Pigs - Alenius, Stefan (1978)
When applied topically, trisodium phosphonoformate (PFA) displayed activity against established cutaneous herpesvirus infections in guinea pigs similar to that exhibited by the closely related phosphonoacetic acid (PAA); however, unlike PAA, PFA was not locally skin irritating. The therapeutic benefits of topical application of PFA were clearly evident when application was delayed for 48 h after virus inoculation, at which time lesions were well developed. The therapeutic effect was dependent on the concentration of PFA and the duration of treatment. PFA exhibited significant activity against established infections when administered intraperitoneally, although it was less effective via this systemic route than when applied topically.